Optimalisasi Kombinasi Cabang Usahatani tanaman Sayuran di Wilayah Transmigrasi Desa Sawahan Kecamatan Cerbon Kabupaten Barito Kuala - Karimal Arum Shafriani; Yudi Ferrianta; Umi Salawati (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Each of transmigrants in the Desa Sawahan wasgiven two parcels of land of 1 ha for crop cultivation and 0.5 ha for housing and home garden as their livelihood;and todevelop the agricultural area. In order to survive, they cultivate various crops and vegetables in those spacious lands. However, farmers have less concern in optimizing their land. By this fact,a linear programming model is needed to determine the optimal combination of vegetables which give maximum income. The study calculates the total cost and income from combination of vegetable cultivation , calculate the income of optimized combination, and estimate the optimized combination which gives maximum revenue. On average, farmers spend IDR 2,222,041 per season on the farming patt ern I and generate income IDR 4,556,521 per season. Meanwhile, total cost and incomeon farming pattern II are IDR 2,121,956 and IDR 4,816,312, respectively. The optimization increases farmer incom e of about 5.28 percent and 8.12 percent for farming pattern I and II , accord ingly. The farming pattern II (chili - bean) is advised as it has higher income (IDR 5,207,174).